Duolingo in English education: Evidence-based perspectives on learning outcomes - F. Fitriani (Curricula)
The proliferation of Mobile-Assisted Language Learning (MALL) applications has reshaped the landscape of language education, with platforms like Duolingo making language learning more accessible, engaging, and flexible. This study systematically reviews 20 research articles to evaluate Duolingo’s effectiveness in fostering language proficiency, with a focus on vocabulary acquisition, reading comprehension, speaking, listening, and writing skills. The findings indicate that Duolingo is particularly effective at building foundational vocabulary and supporting beginner-level reading and listening comprehension through gamified and personalized learning features. Duolingo’s gamified elements enhance engagement and promote consistent practice, but the platform’s lack of interactive, real-time communication restricts its ability to develop higher-order language skills. This study underscores the complementary role of digital tools like Duolingo within language curricula, particularly in blended or hybrid learning models, where mobile learning can support vocabulary retention and independent study. Findings from this study contribute to the ongoing discourse on the role of MALL in language acquisition, offering practical insights for educators and policymakers considering digital integration in language programs.